THE RELATIONSHIP BETWEEN PROFITABILITAS AND COMPANY VALUE IN SUB INDUSTRI HEAVY CONSTRUCTIONS & CIVIL ENGINEERING - Dian Ermayanti; Nekky Rahmiyati (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The purpose of this study was to examine the effect of activity, liquidity, capital structure on firm value with profitability as a mediating variable in Sub Industri Heavy Constructions & Civil Engineering listed on the Indonesia Stock Exchange for the 2018-2021 period. The population in this research is the Sub Industri Heavy Constructions & Civil Engineering listed on the IDX for the 2018 2021 period, totaling 23 companies. After taking the sample using the purposive sampling method, a sample of 10 companies was obtained. The technique of collecting data is by studying documentation from financial reports published on the website www.idx.co.id and the websites of each sample company. The research method is quantitative and uses Partial Least Squares (PLS), which is a Structural Equation Models (SEM) approach that allows researchers to analyze relationships simultaneously. The results showed that Liquidity and Capital Structure directly affect the company’s value. However, activity and profitability directly do not affect the company value. Liquidity , Capital Structure and activity directly do not affect the Profitability. Profitability can does not mediate the influence of Liquidity , Capital Structure and activity on company value.